Role of TGF-?1 in Urinary Bladder Carcinoma - Baghdad Science Journal (مجلة بغداد للعلوم, 2014)
The present study aimed to evaluate sera TGF- ?1 concentration in patients with urinary bladder carcinoma (UBC). All malignant of them was transitional cell carcinoma (TCC) type , patients with urinary bladder disorders (UBD ) and healthy control , and to study the correlation between sera TGF-?1 levels and tumor stages and grades in UBC patients . A direct ELISA test was used to quantify the seraTGF-?1 concentrations in sera of 58 patients with urinary bladder carcinoma UBC of different grades (G) and stages (T) all malignant of them was transitional cell carcinoma (TCC) type , 15 from patients with UBD and 15 healthy subjects . Sera levels of TGF-?1 were elevated in patients with UBC and UBD compared to healthy (P ? 0.01) .There was no association between tumor stages and serum level of TGF-?1 (P?0.05) . Whereas there was an association between serum levels of TFG-?1 and tumor grades (p ?0.05) . Increased serum level was found in high grades G?2 of patient with UBC .